Coupled earthquakes and resonance processes during the uplift of Campi Flegrei caldera - Giacomo Rapagnani; Simone Cesca; Gilberto Saccorotti; Gesa Petersen; Torsten Dahm; Francesca Bianco; Francesco Grigoli (Communications Earth & Environment)
Abstract The Campi Flegrei caldera is a large volcanic complex, with a long history of volcanic activity, located beneath the metropolitan area of Naples, Italy. It is characterised by an intense hydrothermal activity, episodes of localised ground deformation and earthquake swarms. The ongoing unrest, which began in 2005, triggered by a degassing magma source and subsequent magmatic-hydrothermal interactions, reached an uplift of ~1.4 m. The seismicity increased exponentially, with maximum magnitudes of Md 4.4–4.6 in 2024–2025, the largest ever recorded. Here, we perform a comprehensive analysis of earthquake source mechanisms and waveform similarity. Alongside the abundant shallow volcano-tectonic (VT) earthquakes, associated with brittle failures along the rim of a former caldera structure, we analyse newly observed very long-period (VLP) signals. The VLP source is located at a depth of ~3.6 km between the proposed inflation source and the Solfatara maar, a massive volcanic degassing centre with an increasing CO2 flux. The resonant source, excited by VTs at different locations, illuminates an inclined, gas-filled fracture that has been active over at least 7 years, connecting the inflating reservoir with the shallow brittle processes and surface fumaroles.